Pengaruh Kompensasi, Disiplin Kerja dan Motivasi Kerja terhadap Kinerja Karyawan PT. Eka Silver Gold and Jewelry - Ivan Sahvanul Nawawi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to determine and analyze the influence of compensation, work discipline and work motivation on employee performance at PT. Eka Silver Gold And Jewelry. This type of research is research with a quantitative approach. The population in this study were all employees of PT. Eka Silver Gold And Jewelry. Determination of the sample in the study used non-probability sampling through saturated samples so that the total sample in this study was 50 employees. The data analysis method in this research uses SPSS analysis tools through validity, reliability, classical assumption tests, namely normality test, multicollinearity test, heteroscedasticity test, multiple linear regression, t test, F test and correlation and determination coefficients. The results of this research show that (1) Compensation Variable with a sig value. 0.000 < 0.05, then the compensation variable influences employee performance (2) Work Discipline variable with a sig value. 0.000 < 0.05, then the work discipline variable influences employee performance (3) The work motivation variable with a sig. 0.000 < 0.05, then the motivation variable influences employee performance (4). From the results of these calculations, an Fcount of 25.680 is obtained, which means an Fcount of 25.680 and a sig value. 0.000 < 0.05 so Ho is rejected and H4 is accepted. So the independent variables Compensation, Work Discipline and Work Motivation together have an influence on employee performance at PT. Eka Silver Gold and Jewelry.